Introducing language and intercultural communication - Jackson, Jane, 1954- (Routledge, 2019)
"Introducing Language and Intercultural Communication is a lively and accessible introduction for undergraduates who are new to the study of intercultural communication, with a particular emphasis on the language dimension. Incorporating real-life examples from around the world and drawing on current research, this text argues against cultural stereotyping and instead provides students with a skill-building framework to enhance understanding of the complexities of language and intercultural communication in diverse international settings. Readers will learn to become more attuned to power relations and the ways in which sociopolitical forces can influence language choice/attitudes and the intercultural communication process. Features new to this edition include: revised in-text discussion questions, exercises and examples that aim to engage students and provide a more interactive experience; new material that takes account of key social, cultural and political events such as the refugee crisis, Brexit and the rise of populism in many parts of the world; updated theoretical constructs that reflect recent trends in the area such as criticality in intercultural communication; an updated companion website featuring suggested readings, links to media resources and real-world intercultural scenarios for students, as well as additional in-depth instructor resources featuring test materials, PowerPoints, key terms, extended chapter outlines and sample assignments and syllabi. refreshed references and glossary to enhance understanding of key terms and concepts. This is the essential text for undergraduate students who are new to the field of intercultural communication"--